A high frequency of BRCA mutations in young black women with breast cancer residing in Florida. Issue 23 (19th August 2015) - Pal, Tuya; Bonner, Devon; Cragun, Deborah; Monteiro, Alvaro N.A.; Phelan, Catherine; Servais, Lily; Kim, Jongphil; Narod, Steven A.; Akbari, Mohammad R.; Vadaparampil, Susan T.
Abstract : BACKGROUND: Black women are disproportionately affected with triple‐negative breast cancer and have relatively poor survival. To the authors' knowledge, it is not known to what extent differences in the clinical presentation of breast cancer between non‐Hispanic white women and black women can be accounted for by the presence of mutations in the BRCA1 and BRCA2 genes. The authors sought to evaluate the frequency of BRCA pathogenic variants in a population‐based sample of young black women with breast cancer. METHODS: Black women diagnosed with invasive breast cancer at age ≤50 years from 2009 to 2012 were recruited to the study through the Florida Cancer Registry. Participants underwent genetic counseling, completed a study questionnaire, and consented to release of their medical records. Saliva specimens were collected for BRCA sequencing and large rearrangement testing through multiplex ligation‐dependent probe amplification. RESULTS: A DNA sample was evaluated for 396 women, 49 of whom (12.4%) had a mutation in BRCA1 or BRCA2 . Eight recurrent mutations accounted for 49% of all pathogenic variants. CONCLUSIONS: To the authors' knowledge, the prevalence of BRCA mutations among the Florida‐based sample of young black women with breast cancer in the current study exceeds that previously reported for non‐Hispanic white women. It is appropriate to recommend BRCA testing in all young black women with invasive breast cancer. Cancer 2015;121:4173–4180. © 2015 American Cancer Society . Abstract : In the current study, the BRCA mutation prevalence of 12.4% observed among the population‐based sample of young black women with breast cancer is much higher than that previously reported among white women. These findings suggest that BRCA mutations may account for the higher incidence of breast cancer observed among young black women and therefore it may be appropriate to recommend BRCA testing in all young black women with invasive breast cancer.